PENGARUH KEBIJAKAN DIVIDEN, UKURAN PERUSAHAAN, DAN LEVERAGE PERUSAHAAN TERHADAP REAKSI PASAR - Violita, Selvya; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to test (1) the influence of dividend policy to the market reaction, (2) the influence of firmsize to the market reaction and (3) the influence of leverage to the market reaction in the Tourism Companies,hotels, and restaurants which are listed in Indonesia Stock Exchange. This research is causal comparativeresearch. The research population is tourism companies, hotels, and restaurants which are listed in IndonesiaStock Exchange (IDX) in 2007-2014 periods and the numbers of the population are 20 companies. The sampleshave been selected by using purposive sampling method, and there are 5 tourism companies, hotels, andrestaurants which have met the criteria as the research sample. The data has been obtained from the IndonesianCapital Market Directory (ICMD) and the Investment Gallery of Indonesia Stock Exchange (STIESIA)Surabaya. The data analysis technique has been carried out by using classic assumption test, multipleregressions and hypothesis test. Meanwhile, the result of t test has proven that: 1) dividend policy has positiveinfluence to the market reaction; 2) Firm size has positive influence to the market reaction; 3) Leverage of thecompany has negative influence to the market reaction.Keywords: Dividend policy, firm size, leverage, market reaction.